1999
DOI: 10.5694/j.1326-5377.1999.tb127818.x
|View full text |Cite
|
Sign up to set email alerts
|

Sudden death due to ischaemic heart disease in young Aboriginal sportsmen in the Northern Territory, 1982‐1996

Abstract: Objective To estimate the incidence of sport‐related sudden cardiac death due to ischaemic heart disease (IHD) in competitive young Aboriginal sportsmen. Setting Northern Territory (NT), 1982‐1996. Design Retrospective case series with cases identified from Australian Bureau of Statistics cause‐of‐death listings and NT coronial autopsy records. Main outcome measures Circumstances and incidence of sport‐related sudden cardiac deaths due to IHD; autopsy findings. Results Between 1982 and 1996, there were eight s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 9 publications
0
18
0
1
Order By: Relevance
“…Other studies have investigated kava's possible longer-term health effects. For instance, kava has been implicated in serious infectious disease [25] and sudden cardiac death in young Aboriginal sportsmen [28]. However, data not yet published shows that we cannot assert confidently that kava use is associated in the long term with increased risk of ischaemic heart disease morbidity and mortality or pneumonia, (Clough et al, unpublished data).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Other studies have investigated kava's possible longer-term health effects. For instance, kava has been implicated in serious infectious disease [25] and sudden cardiac death in young Aboriginal sportsmen [28]. However, data not yet published shows that we cannot assert confidently that kava use is associated in the long term with increased risk of ischaemic heart disease morbidity and mortality or pneumonia, (Clough et al, unpublished data).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…5 Recently it was suggested that kava use may be a risk factor for sudden cardiac deaths among young Aboriginal sportsmen in Arnhem Land populations, especially when coupled with heavy alcohol use. 6,7 Possible mechanisms include abnormal coagulation with enhanced thrombosis, dehydration or arrhythmias. Other health risks for kava users include acute neurological effects 8 and the infectious disease melioidosis, which may be greater among heavy users.…”
Section: Introductionmentioning
confidence: 99%
“…Heavy kava users may become dehydrated and myocardial ischaemia and sudden cardiac death are possible attributable to abnormal coagulation with increased thrombosis and/or arrhythmias. 2 Acute effects of kava may also be mediated by neurological mechanisms. Large doses of kava pyrones can lead to abnormal atrioventricular function, consistent with kava's well known muscle relaxing properties.…”
Section: Discussionmentioning
confidence: 99%
“…1 Circumstantial evidence suggests that kava consumption is associated with ischaemic heart disease (IHD) and sudden cardiac deaths among, particularly, young Aboriginal sportsmen in this population. 2 …”
mentioning
confidence: 99%